2015
DOI: 10.1002/rcm.7440
|View full text |Cite
|
Sign up to set email alerts
|

Application of liquid chromatography/electrospray ionization ion trap tandem mass spectrometry for the evaluation of global nucleic acids: methylation in garden cress under exposure to CuO nanoparticles

Abstract: The MRM quantification proposed here of cytosine-containing nucleosides using their proton-bound homo-dimers as precursor ions proved its utility for the assessment of global methylation of DNA and RNA in plants under stress imposed by CuO NPs. Detection of copper adducts with cytosine-containing ions, and their elimination by washing extracts with Cu(I) chelator, calls for further investigation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 57 publications
1
2
0
Order By: Relevance
“…Some authors hypothesize that 5-methylcytidine (5mC) found in ribosomal, transfer, messenger, and a variety of small RNAs might be involved in the mechanisms underlying epigenetic inheritance; therefore, methylation of total RNA has also been evaluated in this work. In all samples, methylation was lower than 1% and no significant differences were found between exposed and nonexposed plants (Table ), similarly as reported before for Lepidium sativum . On the other part, chromatographic analysis revealed about a 3-fold decrease of total RNA in roots of plants grown in the presence of Se­(IV) with respect to controls (compare C, G signal intensities between exposed and control samples, Figure ).…”
Section: Resultssupporting
confidence: 86%
“…Some authors hypothesize that 5-methylcytidine (5mC) found in ribosomal, transfer, messenger, and a variety of small RNAs might be involved in the mechanisms underlying epigenetic inheritance; therefore, methylation of total RNA has also been evaluated in this work. In all samples, methylation was lower than 1% and no significant differences were found between exposed and nonexposed plants (Table ), similarly as reported before for Lepidium sativum . On the other part, chromatographic analysis revealed about a 3-fold decrease of total RNA in roots of plants grown in the presence of Se­(IV) with respect to controls (compare C, G signal intensities between exposed and control samples, Figure ).…”
Section: Resultssupporting
confidence: 86%
“…Determination of global DNA methylation by UPLC-HRMS dC and 5 mdC were determined using the chromatographic system UPLC Acquity I-class (Waters) coupled with the mass spectrometer Synapt G2-Si (Waters) [44], brie y; 2 µL of each hydrolysed sample were injected in an UPLC Luna Omega C18 100 Å with a 1.6 µm column (150 × 2.1 mm; Phenomenex), maintained at 40°C at a ow rate of 100 µL/min, and eluted with the mobile phases of ammonium formate 10 mM (pH 4) (A) and methanol (B) in the following gradient programme: 0 to 3 min for 5% B, 3 to 7.5 min for 20% B, and 7.5 to 10 min for 5% B. Free nucleosides were detected using a mass spectrometer by the following operation parameters: electrospray ionisation in positive mode (ESI+); capillary voltage, 3000 V; cone voltage, 30 V; source temperature, 120°C; desolvation gas, N 2 ; desolvation gas temperature, 350°C; desolvation gas ow, 800 L/h; acquisition mass range, 50-600 m/z; scan time, 0.4 sec; and data format, centroid.…”
Section: Enzymatic Hydrolysis Of Dnamentioning
confidence: 99%
“…Free nucleosides were detected using a mass spectrometer by the following operation parameters: electrospray ionisation in positive mode (ESI+); capillary voltage, 3000 V; cone voltage, 30 V; source temperature, 120°C; desolvation gas, N 2 ; desolvation gas temperature, 350°C; desolvation gas ow, 800 L/h; acquisition mass range, 50-600 m/z; scan time, 0.4 sec; and data format, centroid. The analytical signals of the ionic dimers [44]+ at m/z 455.19 ± 0.01 Da and 483.22 ± 0.01 were used for dC and 5 mdC quanti cation. Global DNA methylation was calculated as the molar ratio of [5 mdC/(dC + 5 mdC)].…”
Section: Enzymatic Hydrolysis Of Dnamentioning
confidence: 99%